2010
DOI: 10.5539/ach.v2n2p148
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Predicting Students’ Satisfaction with University Hostels, Case Study, Universiti Sains Malaysia

Abstract: This study was administrated to undergraduate students living in the various hostels of Universiti Sains Malaysia. The primary purpose of this study was to identify the most important factors that predict undergraduate students' level of satisfaction with the student hostels they are living in. This paper also explored the difference in the satisfaction levels of students living in hostels within the campus and those living in hostels outside the campus. Based on literature review, it was hypothesized that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 15 publications
2
35
0
2
Order By: Relevance
“…Studies adopted different concepts to describe university dormitories, for instance, halls of residence [34], student accommodation [35], student dormitory [36], catered halls [37] and hostels [38,39]. Despite the conceptual variabilities, studies identified a low level of satisfaction in Nigeria [40], South Africa [41] and Saudi Arabia [42].…”
Section: University Dormitories Evaluation From Occupant Perspectivementioning
confidence: 99%
“…Studies adopted different concepts to describe university dormitories, for instance, halls of residence [34], student accommodation [35], student dormitory [36], catered halls [37] and hostels [38,39]. Despite the conceptual variabilities, studies identified a low level of satisfaction in Nigeria [40], South Africa [41] and Saudi Arabia [42].…”
Section: University Dormitories Evaluation From Occupant Perspectivementioning
confidence: 99%
“…Furthermore, student housing security tenure and freedom are limited compared to family housing. Student housing, is the housing unit for college students to live for the purpose of studies where many young men leave their homes and parents, reside in student housing without parental monitoring and control which is a different experience for new life style, learn how to compromise with other students, endure, tolerant, shared space and facilities and live independently which was described as a transitional phase towards adulthood [12,25,6]. Also student housing offers chances for students to develop attitudes of living and working together in the college environment and to understand further ethos of the college and life [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Higher education (HE) has been growing rapidly in both developed and developing countries especially in the last three decades where many young men are graduating from high schools and gaining access into colleges and universities [7,9,4,2,11,16,12,21,6]. In the last three decades student enrolment has radically raised globally and is expected to increase as [6] described, more "children of baby boomers" are graduating from high schools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the past studies (e.g., [11]) only employed factor analysis to discover the factors that influence the students' satisfaction but the tool alone failed to offer other types of essential 2 Advances in Decision Sciences information for the hostel administration (e.g., type of interactions between attributes and weights of the factors) in deciding efficient strategies. In addition, in several studies, the overall satisfaction score of each hostel under evaluation was simply computed by using the common arithmetic aggregator which presumes independency among attributes.…”
Section: Introductionmentioning
confidence: 99%
“…Following are some of the hostel attributes highlighted in past studies: number of roommates [5]; floor level [6]; recreation area, drain condition, and distance to clinic [7]; thermal comfort, indoor air quality, and furniture quality [8]; hostel maintenance, laundry [9]; internet facilities [10]; fees, room safety, and room size [11]; study room, ATM machine [12].…”
Section: Introductionmentioning
confidence: 99%